2017
DOI: 10.21767/2471-9854.100035
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Trained Primary Health Care Workers in Mental Health Service Delivery across Ogun State Nigeria

Abstract: Background: In developing countries with shortage of mental health professionals, paramedics are trained in the delivery of mental health services. Knowledge of the experience of the trained health workers is useful in evaluating output of service and restructuring training package. This study was undertaken to determine the experience of trained primary health care (PHC) workers in mental health service delivery across Ogun State South west Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It was probable that some of the scarcely diagnosed disorders were 'somatically disguised' at presentation and sufferers sought help for physical complaints rather than psychological distress. A previous study had shown that 25% to 50% of the THWs reported difficulties in diagnosing depression and OSEC using western diagnostic classification (26). Hence depression remains a major hidden morbidity [27,28].…”
Section: Discussion a Improved Access To Mental Healthcarementioning
confidence: 99%
“…It was probable that some of the scarcely diagnosed disorders were 'somatically disguised' at presentation and sufferers sought help for physical complaints rather than psychological distress. A previous study had shown that 25% to 50% of the THWs reported difficulties in diagnosing depression and OSEC using western diagnostic classification (26). Hence depression remains a major hidden morbidity [27,28].…”
Section: Discussion a Improved Access To Mental Healthcarementioning
confidence: 99%
“…37 It has, however, been reported that though women are twice as likely to experience depression and suicidal ideation than men, but men were four times more likely than women to commit suicide. 41…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed a high personal fulfillment of the trained Peripheral health centers (PHC) workers in mental health service delivery. There is need for re-training of the PHC workers towards effective service delivery (Timothy et al, 2017). Considering the Global action plan for the prevention and control of NCDs 2013-2020 developed by the World health organization (WHO), will give more significant impact on global NCD mortality, by preventing and well managing NCDs cases (WHO 2017a).…”
Section: Discussionmentioning
confidence: 99%